Soils and landscape evolution of the Serra do Espinhaço Meridional, Brazil (Revista Espinhaço, 2021)
e Serra do Espinhaço Meridional (SdEM) is a mountain range in the orogenic belt range of the Proterozoic Eon, whose lithology is formed mainly by quartzites and phyllites, which originate shallow and acidic soils. Its relief comprises a succession of planing surfaces, such as Chapadão do Couto, separated by dissected areas. e objective of this work was to understand the distribution and characterize the soils of a toposequence, to contribute to the understanding of the evolution of the landscape of Chapadão do Couto and SdEM. Evidence has been found that the Chapadão do Couto planing surface was formed in the Paleocene/ Eocene and dissected intermittently since then, with the soils of the tops and slopes of its hills being formed and eroded cyclically. e depressions were also intermittently filled by mineral and organic sediments. e installation of the drainage network and the formation of the hills began in the Tertiary, while the genesis of current soils began in the Late Pleistocene and the Holocene.
Keywords: planing surfaces; soil toposequence; landscape development; soils; Espinhaço mountain